Livet efter romantiken: Ellen Keys levnadskonst i relation till C.J.L. Almqvist - Henning, Peter (Samlaren, 2025)
This study explores the aesthetical and political connections between Ellen Key (1849–1926) and C.J.L. Almqvist (1793–1866). It also analyzes the standing of romanticism in Sweden around the year 1900. While Key’s interest in Almqvist is well documented, notably in the lecture where she dubs him Sweden’s most modern author, their deeper affinities and differences have not been fully appreciated. A common thread in their works is the desire to blur the lines between art and life, which serves as a starting point for analysis. Both Almqvist and Key seek to create an art of living that revitalizes individuals through aesthetic means, proposing various techniques to infuse everyday life with beauty and sacredness. For both, the concept of a ‘beautiful’ life is likewise a measure of humanity. The study also highlights the contentious aspects of Key’s relationship with Almqvist. Key believed that the idealistic worldview of the early 19th century had been realized through new scientific discoveries, allowing her to rhetorically maneuver beyond the horizon of romanticism in search of a modernity more modern than Almqvist’s.